Principal Management in Improving the Education Quality: A Case of SMA Inshafuddin, Banda Aceh - Junianti, Raudhatul; Yusrizal, Yusrizal; Niswanto, Niswanto (Jurnal Pendidikan Progresif, 2021)
This research aims to examine and analyze the program, the principal in improving the education quality at Inshafuddin Senior High School of Banda Aceh. This research uses the descriptive analysis method with qualitative method. The technique of data collection used are observation, interview, and documentation. The subject of this research are principal, teachers, and supervisors. The result of the research shows that: (1) The preparation of theof the principal’s program includes: a long-term annual program of eight years, a medium-term four-year period and a short-term once a year. (2) The implementation of the principal’s program is carried out by division of tasks, conducting training and attending MGMP, condukting laboratoryn and library monitoring and axamination at the and of each school year and providing guidance for teavchers who are less participating. (3) Evaluation of the program is carred out by the committe team namely the school principal, representatives, senior teachers and supervisors using the intrument and the results of the evaluation aredocumented. (4) The obstacles include: the efficiency of the discipline and the effeciency of the interest in reading students in accalerating.Keywords: principal management, education quality, senior high schoolDOI: http://dx.doi.org/10.23960/jpp.v11.i3.202114